Studies in Law, Politics and Society, 45. - Sarat, Austin (Emerald Group Pub., 2008)
Offers fresh perspectives on sentencing and punishment, lawyering for the public good, and the meaning of legal doctrine. This book contains articles that exemplify the work being done in interdisciplinary legal scholarship.